HERE AND NOW: BREAD AND EVIDENCE - HARUTYUNYAN, EDVARD (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
In different historical periods, there have been staged social-cultural and artistic various practices (bread and scene, bread and faith, bread and ideology) in order to establish an institutional control over the masses’ sacred irrational passions (energy) and spiritual rational ambitions (will). Each of them is a unique culture of the organization and regulation of life, with the help of which the political elite tried and tries to subtly reduce the political drama nominated by the masses for participation in political life into the biological (bread) and artistic (scene) drama. And now, before our very eyes, a grotesque reality is being formed, a new scenario of public life is being staged, where the “here and now living” type of human requires neither a scene nor a faith and nor an ideology from the political elites. He demands an immediate solution to the problems that concern him – bread and evidence.